Developing an Evidence-Based Tool for Planning and Evaluating Vaccination Strategies Aimed at Improving Coverage in Elderly and At-Risk Adult Population - Calabrò, Giovanna Elisa; Carini, Elettra; Tognetto, Alessia; Mancinelli, Silvia; Sarnari, Laura; Colamesta, Vittoria; Ricciardi, Walter; de Waure, Chiara, The BRAVE Project Expert panel (Frontiers in Public Health, 2021)
Background Vaccination coverages need to be constantly maintained and improved with the implementation of vaccination strategies. This paper describes the development of an evidence-based tool to guide their planning and evaluation. Methods A scoping review was performed in MEDLINE and institutional websites to search for similar available tools. A first version of the tool was developed considering review results and a four-step method used for the control and continuous improvement of processes and products, namely the Deming cycle. A panel of eight experts was then involved in a Delphi study for the finalization of the tool that was eventually discussed in a face-to-face meeting. Results The scoping review found only one document and the first version of the tool was composed of 30 items. After the Delphi first round, 11 additional items were suggested and 5 original items amended. After the Delphi second round 41 items were eventually included. During the face-to-face meeting, 7 items were recognized as requisites for setting vaccination strategies, whereas 17 as relevant ones. Conclusions Current public health challenges impose the need for evidence-based tools to organize effective vaccination strategies. Our tool is a first proposal which aims to reflect this focus.